Trends of Catch and Utilization in Rice Field Fisheries among Rural Communities in Cambodia: A Three-Year Analysis - Sean, Vichet; Sithirith, Mak (WorldFish, 2024)
Rice field fisheries (RFF) systems in Cambodia are a basis of rural livelihoods, combining agriculture and aquatic ecosystems to provide critical nutrition and economic benefits. The well managed RFF systems enable households to collect more fish, other aquatic animals (OAA), and plants, sustaining food security and incomes. Between 2021 and 2023, RFF systems contributed significantly to rural diets and biodiversity, with each hectare producing an average of 97 kg of fish, 27 kg of OAA, and 4 kg of aquatic plants annually. These contributions highlight their essential role in building food-secure and resilient communities. Fish and OAA are vital sources of protein and micronutrients in Cambodian diets, with RFF systems accounting for up to 70% of fish consumption in some areas. The wet season’s seasonal abundance ensures affordable and nutrient-rich food, particularly benefiting women and youth who actively engage in collection activities. However, RFF systems face challenges such as environmental stress, water scarcity, and changing agriculture practices, emphasizing the need for sustainable management to preserve their productivity and benefits. By addressing challenges through habitat restoration, strengthening connections between community fish refuges (CFRs) and rice fields, and adopting innovative, climate-resilient farming practices, RFF systems can achieve their full potential. Enhanced governance and active community involvement will play a pivotal role in ensuring long-term sustainability. In the Mekong Delta, where rice fields are dominant, these systems hold immense promise for improving livelihoods, securing food systems, and building resilience against climate change across Cambodia.